2020
DOI: 10.3389/fpsyt.2020.00638
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Auditory and Visual Sensory Discrimination Reflect a Genetic Liability for Psychosis and Predict Disruptions in Global Cognitive Functioning

Abstract: Sensory discrimination thresholds (i.e., the briefest stimulus that can be accurately perceived) can be measured using tablet-based auditory and visual sweep paradigms. These basic sensory functions have been found to be diminished in patients with psychosis. However, the extent to which worse sensory discrimination characterizes genetic liability for psychosis, and whether it is related to clinical symptomatology and community functioning remains unknown. In the current study we compared patients with psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
(81 reference statements)
0
16
0
Order By: Relevance
“…Future investigations may also assess the relationships between sensory discrimination deficits across auditory and visual modalities, as auditory perceptual disruptions are reported as more frequent. Previous studies have suggested a link between the two (Ramsay et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Future investigations may also assess the relationships between sensory discrimination deficits across auditory and visual modalities, as auditory perceptual disruptions are reported as more frequent. Previous studies have suggested a link between the two (Ramsay et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…There is always the possibility that we were not able to detect a true relationship due to the relatively small variation in PANSS scores in our sample, resulting in a type II error. Previous studies have reported associations between impaired sensory discrimination and poor cognitive functioning in people with psychosis that are not solely explained by their psychiatric symptoms (Ramsay et al, 2020). It has been suggested that sensory disruptions, for example in motion processing, are due to higher-order memory processing deficits, caused or influenced by existing disruptions in topdown processes (Brenner, Wilt, Lysaker, Koyfman, & O'Donnell, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances of auditory and visual perception were found in patients with schizophrenia and also among their unaffected first-degree relatives, suggesting a familial/genetic liability behind these alterations (Force et al, 2008;P. Li et al, 2017;Ramsay et al, 2020;Sponheim et al, 2013). In line with the idea that activation of sensory areas are involved in the representation of perceptual experiences (Pearson, 2019), auditory hallucinations were found to correlate with activation in the associative auditory cortex and the superior temporal gyrus (Horga & Abi-Dargham, 2019), while visual hallucinations seem to be accompanied by increased activity of the visual association cortex (F. Waters et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that deficits in sensory processing (i.e., auditory and visual low systems) derived from glutamatergic, and other neurotransmitters dysfunction, may contribute to high-order cognitive impairment in psychosis [41]. Indeed, reduced sensory discrimination in both auditory and visual systems can be associated with worse global cognition, including working memory (WM), in patients with psychosis [42]. Therefore, the observed encoding failures we found in this study might be influenced by a weak sensory representation of stimuli, as proposed by Javitt et al [43].…”
Section: Discussion/conclusionmentioning
confidence: 99%